PREVALENCE, ASSOCIATED FACTORS, AND HELP SEEKING BEHAVIOR RELATED TO PSYCHOLOGICAL DISTRESS AMONG INTERNATIONAL STUDENTS AT UNIVERSITI KEBANGSAAN MALAYSIA - Ismail, Aniza; Mohsen Kahwa, Khadiga (Malaysian Journal of Public Health Medicine, 2020)
Depression, anxiety, and stress are associated with decreased role functioning, productivity, and quality of life. International students are more prone to psychological distress as they face many stressors while studying abroad. The objectives of the study were to determine the prevalence and associated factors of depression, anxiety, and stress among international students, their help-seeking behavior and their awareness of the available on-campus mental support services. A cross-sectional study with a purposive sampling method was performed on 280 international students at Universiti Kebangsaan Malaysia (UKM) between the age of 18 and 35 years. The Depression Anxiety Stress Scale-21 (DASS-21) questionnaire was used anonymously to assess the mental health of students. Soci-demographic, help-seeking behavior, and awareness data were obtained. Independent sample t-test, one-way Analysis of Variance (ANOVA) test, and Multiple Linear Regression were used to explore associated factors. The overall prevalence of depression, anxiety, and stress among international students was 58.9%, 71.8%, and 53.9% respectively. Age was significantly associated with depression and anxiety. Ethnicity showed a significant association with depression and stress. No other factors were found to be significantly associated with psychological distress. Only 9.6% of the international students had sought help from on-campus mental support services. Students who were aware of the presence of such services were only 21.4% of the participants. In conclusion, the recent study showed a high prevalence of psychological distress and low help-seeking behavior among international students in Malaysia. This provided data that could be used in intervention programs to improve the mental health of the increasing number of international students in Malaysia.